Three‐dimensional virtual navigation versus conventional image guidance: A randomized controlled trial. (14th April 2016) - Dixon, Benjamin J.; Chan, Harley; Daly, Michael J.; Qiu, Jimmy; Vescan, Allan; Witterick, Ian J.; Irish, Jonathan C.
Abstract : Objectives/Hypothesis: Providing image guidance in a 3‐dimensional (3D) format, visually more in keeping with the operative field, could potentially reduce workload and lead to faster and more accurate navigation. We wished to assess a 3D virtual‐view surgical navigation prototype in comparison to a traditional 2D system. Methods: Thirty‐seven otolaryngology surgeons and trainees completed a randomized crossover navigation exercise on a cadaver model. Each subject identified three sinonasal landmarks with 3D virtual (3DV) image guidance and three landmarks with conventional cross‐sectional computed tomography (CT) image guidance. Subjects were randomized with regard to which side and display type was tested initially. Accuracy, task completion time, and task workload were recorded. Results: Display type did not influence accuracy ( P > 0.2) or efficiency ( P > 0.3) for any of the six landmarks investigated. Pooled landmark data revealed a trend of improved accuracy in the 3DV group by 0.44 millimeters (95% confidence interval [0.00–0.88]). High‐volume surgeons were significantly faster ( P < 0.01) and had reduced workload scores in all domains ( P < 0.01), but they were no more accurate ( P > 0.28). Conclusion: Real‐time 3D image guidance did not influence accuracy, efficiency, or task workload when compared to conventional triplanar image guidance. The subtle pooled accuracy advantage for the 3DV view is unlikely to be of clinical significance. Experience level was strongly correlated to task completion time and workload but did not influence accuracy. Level of Evidence: N/A. Laryngoscope, 126:1510–1515, 2016